Efisiensi Agronomi Pupuk Granul Urea-Biochar Bambu Berselaput Arabic Gum Pada Pertumbuhan Tanaman Bawang Merah (Allium ascaloniucm L.) - Dewa Ayu Ari Febriyanti; Luh Anggreni Dewi (CV. Ulil Albab Corp, 2024)
Excessive application of urea fertilizer to shallots will have a negative impact on the environment and environmental pollution because a lot of N is lost from the plants. The loss of fertilizer nitrogen from the soil occurs through the leaching process. The way to increase the effectiveness of fertilizer use is to modify the fertilizer so that it forms a slow release fertilizer. The use of biochar as an environmentally friendly organic material as a carrier for slow release urea fertilizer has great potential because it is easy to obtain and easy to make. Biochar is a carbon-rich product obtained by heating biomass in low or oxygen-free conditions. The research was carried out in the greenhouse of the UPT Center for Pest and Plant Disease Control, Celuk Sukawati Village, Gianyar, this research was arranged in a Completely Randomized Design with a single factor consisting of 9 treatments and repeated 3 times. The research results showed that plant height showed the highest value in the M25 treatment and the highest RAE value was in the M25 treatment, namely 374%, indicating a higher value compared to the recommended standard fertilizer treatment (U1B0). Further research is needed regarding the formulation of the composition for making Arabic gum-coated granule fertilizer.